TOTAL THYROIDECTOMY AS PREFERRED OPTION FOR BENIGN DISEASE– OUR EXPERIENCE OF 152 CASES - Ata Ul Lateef; Muhammad Sajid (Journal of University Medical & Dental College, 2012)
ABSTRACT Background: Type of study: Experimental. Study design: Case series. Place and duration of study: It was conducted in surgical unit-4 DHQ Hospital, Punjab Medical College, Faisalabad from January 2009 to December 2011. Objectives: To evaluate the safety of total thyroidectomy for benign disease in terms of permanent complications i.e. Hypoparathyroidism and Recurrent Laryngeal Nerve (RLN) damage. Methods: One hundred and fifty two patients with benign enlargement of thyroid gland (Multinodular, euthyroid and toxic goiters, Grave’s disease) underwent total thyroidectomy from January 2009 till December 2011. Evaluation of results was done by analyzing the data in SPSS Version-17. Parathyroids were identified pre-operatively and Recurrent Laryngeal Nerve (RLN) traced throughout its course.1 Results: Fourteen patients presented with transient post-operative hypocalcaemia (9.2%). Only one patient developed permanent Hypoparathyroidism (0.6%), confirmed by estimating parathormone levels in blood. One patient developed permanent unilateral RLN injury (0.6%). No patient developed bilateral RLN injury (0%). Two patients developed hematoma due to reactionary hemorrhage necessitating re-opening and securing of bleeding vessel (1.2%). Six patients (3.9%) developed serous collection post-operatively and were treated successfully with aspiration alone. There was no mortality (0%). Conclusion: Total thyroidectomy (TT), if performed by experienced surgeons is quite safe and preferred option for management of benign thyroid disease to avoid future reocurrences